The Life Experience of Patients With Coronary Heart Disease Post Percutaneous Coronary Intervention (PCI) in Bulukumba Regency - Annisya Cahya Amsani; Muriyati Muriyati; Amirullah Amirullah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2021)
Coronary Heart Disease is a disease that interferes with heart function due to narrowing that occurs due to fatty deposits or plaque in the coronary arteries that block blood flow to the heart. The existence of a non-surgical PCI (Percutaneous Coronary Intervention) procedure which dilates blood vessels with the installation of a stent, makes many patients with coronary heart disease choose to undergo this procedure. The high number of choices for PCI action and the lack of research that discusses the life experiences of patients who have undergone PCI, makes researchers interested in conducting this study. This study aims to determine the life experiences of patients with coronary heart disease who have undergone percutaneous coronary intervention in Bulukumba Regency. The data in this study were collected through in-depth interviews on selected subjects (In-depth Interview) and analyzed using Thematic Analysis. Researchers found 4 themes from the results of data analysis. The themes are: (1) Lifestyle, sub-themes: diet, smoking, physical activity and medication adherence. (2) Psychological responses, sub themes: feelings of anxiety and worry, emotions and stress. (3) Forms of Support, sub-themes: family support, spiritual support. (4) Quality of Life for Post PCI Patients, sub-themes: feeling back to normal, changes in sleep patterns and pain. There are 4 themes found in this study. It is hoped that patients with coronary heart disease who have undergone PCI procedures will continue to increase their motivation to live a better life.